A RARE CASE OF INVASIVE PAPILLARY CARCINOMA OF BREAST - Saxena, Divish; Akhtar, Murtaza; Rode, Avinash; Kundra, Dhruv (International Journal of Clinical and Biomedical Research, 2015)
Papillary carcinoma of the breast is extremely rare variety of carcinoma breast with a mere incidence of only 0.5% of all recently diagnosed cases of breast cancer. We present a case of 63 years old postmenopausal female who came to surgical outpatient department with complaints of a slowly increasing mass in the left breast of 1 month duration which was painless. A Left-sided modified radical mastectomy was performed with an absolutely normal post operative period. The final histopathology report was suggestive of invasive papillary carcinoma. We report this case as it is rarely diagnosed. KEYWORDS: Invasive papillary carcinoma; Modified radical mastectomy; Carcinoma breast.